PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK HERBORIST DI KOTA SEMARANG - Rudika Harminingttyas; Th. Susetyarsi; Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
Thisi studyii aimsii toii investigateii theii impactii ofii greenii marketingii strategiesii onii consumerii purchasingii decisionsii forii Herboristii productsii inii Semarangii city.ii Theii natureii ofii thisii studyi isi ani explanatoryi studyi withi ai quantitativei approach.i Thei variablesi usedi ini thisi studyi arei environmentali awarenessii (X1),ii greenii productii featuresi (X2),ii “Greenii Productii Price”(X3),ii “Greenii productii Promotion”ii (X4),ii andii purchaseii decisionii (Y).ii Theii studyii groupii isii peopleii whoii liveii inii Sewmarangii cityii andii areii consumersii ofii Herborist   products.ii Theii totalii sampleii forii thisii surveyi includesi overi 113i respondents.i Datai collectioni methodi usingi surveysi distributedi ini Googlei Forms.i Thei datai analysisi usedi isi multiplei lineari regressioni analysis.i Asii aii resultii ofii theii analysis,ii theii variablesii environmentii Awarenessi (X1),ii greenii productii Features (X2),ii “Greenii Productii Price”ii (X3),ii andii greenii productii Promotionii (X4)ii i Purchaseii decisionsii (Y).